2021
DOI: 10.1038/s43016-021-00320-x
|View full text |Cite
|
Sign up to set email alerts
|

Geographically targeted surveillance of livestock could help prioritize intervention against antimicrobial resistance in China

Abstract: ntimicrobials are used in agriculture as disease treatments, prophylactically to prevent infections in healthy animals and to increase productivity 1 . However, the routine use of antimicrobials as surrogates for good hygiene practices on farms 2,3 is driving a rise in antimicrobial resistance (AMR), with increasingly serious consequences for animal health 1,4 and potentially for human health 5,6 .Globally, 73% of antimicrobials are used in animals 7 , with China being the largest consumer of antimicrobials in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Our study confirms the importance of considering the landscape scale when investigating the determinants of AMR (Singer et al., 2006 ; Zhao et al., 2021 ). Here, we could interpret our results in terms of sources and sinks of resistance.…”
Section: Discussionsupporting
confidence: 88%
“…Our study confirms the importance of considering the landscape scale when investigating the determinants of AMR (Singer et al., 2006 ; Zhao et al., 2021 ). Here, we could interpret our results in terms of sources and sinks of resistance.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, we also found the AMR rate of most antimicrobials of human origin isolates decreased in 2012, which was probably influenced by the policy for antimicrobial management ( http://www.gov.cn/flfg/2012–05/08/content_2132174.htm ). A recent study reported that the prevalence of resistance in Salmonella showed an increased trend after 2010 in penicillin in chicken, and in sulfonamide, penicillins, and tetracycline in pigs [ 22 ]. A similar landscape was also observed in other countries, for example, the prevalence of MDR was generally low ranging from 3.4% in 1984 to a high of 9.7% in 2013 in Australia [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent works have shown that resistance levels in humans and animals can vary at a fine spatial scale, and accumulation of resistance genes in those areas may create geographic hotspots for AMR (2,9). Identifying geographic hotspots of AMR within countries could help with targeting interventions against AMR, such as improved farm biosecurity and targeted surveillance, where they might have the greatest benefits (10)(11)(12).…”
Section: Researchmentioning
confidence: 99%